(untitled) (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2026)
This study advances Symbiosophy or Symbiosophies, a groundbreaking philosophical paradigm coined and espoused by Elias Ifeanyi E. Uzoigwe, as a transformative framework for reimagining intercultural philosophy in an age of profound global interdependence. At its core lies the argument that mutual dependence is not merely a social ideal but the foundational principle of reality, knowledge, and ethical life. Against the homogenizing tendencies of universalism and the fragmenting impulses of relativism, Symbiosophies articulates a relational philosophy in which human existence, personhood, and moral responsibility are fundamentally co-constituted. The study aims to develop a robust comparative paradigm for understanding how African, Eastern, and Western philosophical traditions conceptualize interdependence, coexistence, and human flourishing. Specifically, it examines convergences and divergences among African communitarianism, Eastern relational metaphysics, and Western dialogical and ecological thought; critiques the limitations of universalist and relativist models; and formulates Symbiosophies as a global philosophy for intercultural dialogue. Employing a Symbiosophic-comparative-hermeneutic methodology, the study integrates textual analysis, intercultural interpretation, and philosophical reconstruction. Its findings reveal a profound, though often under-theorized, convergence across traditions: reality is relational, knowledge is dialogical, and ethics arises from interconnected existence. Symbiosophies offers a non-hegemonic model of pluralistic universality, one that preserves cultural particularity while enabling shared ethical horizons via dialogical reciprocity and relational accountability. By redefining universality as relational and relativism as dialogically accountable, it emerges as a vivacious 21st-century philosophy. The study concludes by recommending Symbiosophies as a foundational framework for comparative philosophy, global ethics, intercultural solidarity, peacebuilding, environmental stewardship, sustainable coexistence, and policy discourse aimed at fostering epistemic justice in an increasingly interconnected world.